2022
DOI: 10.1186/s13321-022-00639-y
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the mutation effects of protein–ligand interactions via end-point binding free energy calculations: strategies and analyses

Abstract: Protein mutations occur frequently in biological systems, which may impact, for example, the binding of drugs to their targets through impairing the critical H-bonds, changing the hydrophobic interactions, etc. Thus, accurately predicting the effects of mutations on biological systems is of great interests to various fields. Unfortunately, it is still unavailable to conduct large-scale wet-lab mutation experiments because of the unaffordable experimental time and financial costs. Alternatively, in silico compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 67 publications
2
10
0
Order By: Relevance
“…The binding free energy for the six complexes was calculated using fastDRH [ 30 ], an online web server, by submitting the cartesian coordinates of the corresponding receptor molecule and the ligand molecule. For binding free energy calculation, we have used PB4 MM/PBSA procedure based on the pose ranking.…”
Section: Methodsmentioning
confidence: 99%
“…The binding free energy for the six complexes was calculated using fastDRH [ 30 ], an online web server, by submitting the cartesian coordinates of the corresponding receptor molecule and the ligand molecule. For binding free energy calculation, we have used PB4 MM/PBSA procedure based on the pose ranking.…”
Section: Methodsmentioning
confidence: 99%
“…Here, Molecular Mechanics/Generalized Born Surface Area (MM/GBSA) was used to analyze the binding characteristics of the cMD and US trajectories, which has been widely applied in various biological systems, such as protein–ligand, protein–protein/peptide, , and protein–RNA systems. The calculation of MM/GBSA binding free energy follows the below formulas: .25ex2ex Δ G bind = Δ G com false( normalΔ G rec + normalΔ G lig false) .25ex2ex G bind = Δ H T Δ S Δ E MM + Δ G sol T Δ S .25ex2ex Δ E MM = Δ E int + Δ E ele + Δ E vdw .25ex2ex Δ G sol = …”
Section: Methodsmentioning
confidence: 99%
“…Here, Molecular Mechanics/Generalized Born Surface Area (MM/GBSA) was used to analyze the binding characteristics of the cMD and US trajectories, which has been widely applied in various biological systems, such as protein–ligand, protein–protein/peptide, , and protein–RNA systems. The calculation of MM/GBSA binding free energy follows the below formulas: where Δ G bind represents the binding free energy that is numerically equal to the energy difference between the protein–ligand complex (bound state) and the protein/ligand individuals (free state) (eq ).…”
Section: Methodsmentioning
confidence: 99%
“…In most studies using this method, the interior dielectric constant is set to one when calculating the electrostatic energy (the Coulomb term in the force field) and polar solvation energy. However, multiple studies have shown that an interior dielectric constant of one is not appropriate for some systems. , Using a small solute dielectric constant leads to an overestimation of the electrostatic attractions and repulsions between the protein and the ligand because electrostatic interactions are not shielded enough. Hou et al found that in most cases, MM/PB­( GB )­SA produces better results with a higher dielectric constant, such as 2 or 4 .…”
Section: Introductionmentioning
confidence: 99%